2022
DOI: 10.1111/jonm.13623
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the Mandarin version of the Trust in Nurses Scale

Abstract: Aims: This study aimed to translate and validate the Trust in Nurses Scale (TINS) and then test and implement the tool.Background: Trust is the core feature of the nurse-patient relationship, and a simple and universal instrument to measure patients' trust in nurses in China is lacking.Methods: Exploratory and confirmatory factor analyses (EFA and CFA) were performed to verify structural validity. Content validity and reliability analyses were also conducted.Results: The Cronbach's alpha of the TINS was .817, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 24 publications
(40 reference statements)
0
9
0
Order By: Relevance
“…Y. Kim et al, 2022). In addition, most journal with high publications and citations are international top journal of nursing, such as Journal of Nursing Management, Journal of Clinical Nursing, International Journal of Nursing Studies, Nurse Education Today, etc., suggesting the application of SEM has become a hotspot in the field of nursing internationally (Liu et al, 2022;Margadant et al, 2021;Santo et al, 2022;Zhu et al, 2019). Furthermore, some journals with high publications, centrality, and citations were not of the nursing field, such as Journal of the American Geriatrics Society, Journal of the American Medical Directors Association, American Journal of Epidemiology, Advances in Parasitology, British Journal of Psychiatry, Archives of General Psychiatry, and Age and Aging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Y. Kim et al, 2022). In addition, most journal with high publications and citations are international top journal of nursing, such as Journal of Nursing Management, Journal of Clinical Nursing, International Journal of Nursing Studies, Nurse Education Today, etc., suggesting the application of SEM has become a hotspot in the field of nursing internationally (Liu et al, 2022;Margadant et al, 2021;Santo et al, 2022;Zhu et al, 2019). Furthermore, some journals with high publications, centrality, and citations were not of the nursing field, such as Journal of the American Geriatrics Society, Journal of the American Medical Directors Association, American Journal of Epidemiology, Advances in Parasitology, British Journal of Psychiatry, Archives of General Psychiatry, and Age and Aging.…”
Section: Discussionmentioning
confidence: 99%
“…This result indicated that the nursing and other disciplines have formed multidisciplinary researches based on the application of SEM, especially in the field of psychiatry and psychology (Aloisio et al, 2019;Casten et al, 1998;Tang et al, 2022;Temkin-Greener et al, 2020;Timakum et al, 2022). With the increasing burden caused by mental disorders, psychiatry and psychological health among population have raised increased concern (Liu et al, 2022). The mechanism of the relationships between psychological variables are usually complicated and difficult to explore or confirm by simple statistical methods.…”
Section: Discussionmentioning
confidence: 99%
“…Item analysis includes critical ratio (CR), correlation analysis, Cronbach's α test and factor analysis. Items are deleted when they do not meet two or more of the following criteria: (1) the CR was significant, and should be >3; (2) the correlation between item scores and total scores, and should be significant and >0.40; (3) the Cronbach's α after deleting an item is smaller than the Cronbach's α of the total scale before deleting it; (4) factor loading of the items were >0.45; (5) item commonalities were >0.20 (Liu et al, 2022).…”
Section: Item Analysismentioning
confidence: 99%
“…A significant correlation ranged from 0.40 to 0.80 indicated good criterion-related validity of the scale. The convergent validity was represented by the Average Variance Extracted (AVE), which should be >0.50 (Liu et al, 2022). The discriminant validity is illustrated by comparing the square root of AVE of each factor with the correlation coefficient of this factor and any other factor.…”
Section: Criterion-related Validity Convergent and Discriminant Validitymentioning
confidence: 99%
See 1 more Smart Citation